Is it Time to Move On? Reflections on a Research Agenda for Self-Directed Learning in the 21st Century - Ralph G. Brockett (Adult Education Research Conference, 2000)
Self-directed learning has been one of the most studied areas of adult education over the past three decades. Instead of abandoning this line of inquiry, more research is needed that explores the topic from new perspectives